Spraying and plating production process for carbon fiber roller

By constructing a nano-palladium catalytic layer on the surface of carbon fiber rollers through plasma etching activation and low-temperature composite chemical plating, the problems of thermal damage, insufficient bonding force and environmental protection of traditional carbon fiber roller surface treatment devices are solved, and high-performance and environmentally friendly carbon fiber roller surface treatment is achieved.

CN120888912APending Publication Date: 2025-11-04JINJIANG JINGYANG COT MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511094999.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-06
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing carbon fiber roller surface treatment equipment suffers from problems such as high-temperature operation leading to thermal decomposition of the substrate, insufficient adhesion between the coating and the substrate, and environmental issues caused by chromium and cyanide plating solutions, failing to meet the requirements of high-performance and green production.

Method used

The process employs plasma etching activation, catalytic activation, and low-temperature composite chemical plating. By constructing micron-level roughness and oxygen-containing functional groups on the surface of carbon fiber rollers, combined with ultrasonic-assisted palladium catalytic deposition of a nano-palladium layer, a Ni-P-SiC composite coating is deposited using a chromium-free and cyanide-free formulation. The coating thickness and porosity are controlled, and the coating is then subjected to heat treatment and mechanical polishing.

Benefits of technology

It improves the adhesion between the coating and the substrate, avoids the risk of thermal damage and hydrogen embrittlement to the substrate, enhances the impact toughness and adhesion of the coating, reduces wastewater treatment costs, and achieves high-performance and environmentally friendly production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120888912A_ABST
    Figure CN120888912A_ABST
Patent Text Reader

Abstract

The invention discloses a production process for composite chemical plating on the surface of a carbon fiber roller. The production process comprises the steps of plasma etching activation, catalytic activation, low-temperature composite chemical plating and aftertreatment. A rough surface and an oxygen-containing functional group are constructed through argon / oxygen mixed plasma etching, ultrasonic-assisted palladium-tin catalysis is used for enhancing a combined anchor point, a Ni-P-SiC composite coating is deposited at the temperature of 65-85 DEG C in combination with dynamic rotation and pulse stirring, and machining is completed through nitrogen protection heat treatment and polishing. The process solves the problems of matrix thermal damage, hydrogen embrittlement risk, coating spalling and environmental protection of a traditional process, the binding force of a plating layer is improved to be larger than or equal to 25 MPa, the porosity is smaller than or equal to 0.5%, the matrix strength retention rate is larger than 95%, the wastewater treatment cost is reduced by 60%, and the process is suitable for surface treatment of the high-performance carbon fiber roller.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention provides a production process, and particularly relates to a carbon fiber roller spraying and coating production process. Background Technology

[0002] The carbon fiber roller surface treatment device is a device for modifying the surface of carbon fiber composite rollers. Its main function is to impart properties such as wear resistance, corrosion resistance, and oxidation resistance to the rollers through plating or coating to meet the high precision and high stability requirements of industries such as printing and film manufacturing.

[0003] Existing carbon fiber roller surface treatments mostly employ traditional electroplating or high-temperature chemical plating equipment. The basic structure includes an electroplating tank / plating solution tank, a heating system, hangers, and a stirring device. By immersing the roller in a solution containing metal ions, a coating is formed through electrolysis or chemical reduction. However, such equipment has significant shortcomings: high-temperature operation (usually above 100°C) easily leads to thermal decomposition of the carbon fiber resin matrix, resulting in hydrogen embrittlement that reduces the matrix strength by more than 30%. The bonding strength between the coating and the matrix is ​​less than 10 MPa, making it prone to peeling. Furthermore, plating solutions containing chromium and cyanide cause serious environmental problems, failing to meet the requirements of high-performance and green production. Summary of the Invention

[0004] In order to solve the above problems, this application provides a carbon fiber roller spraying and coating production process, which solves the problems of substrate thermal damage, hydrogen embrittlement risk, coating peeling and environmental protection of traditional processes, and improves adhesion and production compliance.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a composite chemical plating production process for carbon fiber rollers, comprising the following steps:

[0006] (1) Plasma etching activation: In a vacuum environment of 0.1-10 Pa, argon / oxygen mixed plasma with a power of 1-5 kW is used to etch the carbon fiber roller substrate for 10-30 minutes to improve the surface roughness to Ra1.0-3.0 μm and generate oxygen-containing functional groups.

[0007] (2) Catalytic activation: The roller body treated in step (1) is immersed in a palladium-tin colloidal activation solution, wherein Pd 2+ Concentration of 50-200 mg / L, Sn 2+ With a concentration of 1-5 g / L and a pH of 1.5-2.5, a nano-palladium catalyst layer is formed by deposition for 5-15 minutes under ultrasonic assistance at a frequency of 40-100 kHz.

[0008] (3) Low-temperature composite chemical plating: The activated roller is placed in a chemical plating solution for plating. The plating solution consists of: 20-30 g / L nickel sulfate, 25-35 g / L sodium hypophosphite, 40-60 g / L of a composite complexing agent consisting of a combination of sodium citrate and glycine, 5-15 g / L of nano-silicon carbide particles with a particle size of 50-200 nm, 0.1-0.5 g / L of sodium dodecyl sulfonate as a surfactant, and 1-5 mg / L of thiourea as a stabilizer. The plating conditions are: temperature of 65-85℃, which is 20-30℃ lower than that of the traditional process, pH value of 4.5-5.5, roller rotation speed of 10-30 rpm, and plating time of 60-180 minutes.

[0009] (4) Post-treatment: The plated roller is cleaned with deionized water, heat-treated in hot air circulation at 180-220℃ for 1-2 hours, and finally mechanically polished until the surface roughness Ra≤0.1μm.

[0010] Preferably, in step (1), the gas ratio of the plasma is Ar:O2 = 4-6:1, and the oxygen content on the surface is increased to 15-25 at% after etching.

[0011] Preferably, the nano-silicon carbide particles in step (3) are pretreated with silane coupling agent KH-550. The pretreatment method is as follows: the nano-particles are dispersed in an ethanol solution with a concentration of 1-5wt%, ultrasonically treated for 30 minutes, and then centrifuged and dried.

[0012] Preferably, in step (3), the plating solution is pulsed and stirred, specifically by alternately turning the stirrer on and off at a frequency of 5-10Hz, with each cycle being 30 seconds on and 10 seconds off.

[0013] Preferably, the heat treatment in step (4) is carried out under a nitrogen protective atmosphere, and the heating rate is ≤5℃ / min.

[0014] Preferably, the final coating is a Ni-P-SiC composite structure, wherein the phosphorus content is 8-12wt%, the SiC dispersed phase accounts for 5-10vol%, the coating thickness is 20-50μm, the porosity is ≤0.5%, the bonding strength is ≥25MPa, and the coating strength is measured according to ASTM C633 standard.

[0015] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages:

[0016] This device primarily addresses the challenges of substrate damage, hydrogen embrittlement, coating peeling, and environmental compliance inherent in traditional electroplating / chemical plating processes. It constructs micron-level roughness and oxygen-containing functional groups on the surface of a carbon fiber roller through plasma etching activation, combined with ultrasonic-assisted palladium catalysis to enhance bonding anchors. Then, a low-temperature composite chemical plating process at 65-85℃ is employed to deposit a Ni-P-SiC nanocomposite coating under dynamic rotation and pulse stirring. Specifically, low-temperature operation (below the Tg temperature of the carbon fiber resin matrix) prevents matrix decomposition, and nitrogen-protected heat treatment completely eliminates hydrogen permeation, ensuring a substrate strength retention rate exceeding 95% to eradicate hydrogen embrittlement and thermal damage. Plasma activation increases bonding strength by 3 times (exceeding 25 MPa), and the use of nano-SiC particles for toughening increases the coating's impact toughness by 50% (not less than 3 J / cm). 2 The process balances hardness (HV800-1000) and ductility with a medium phosphorus content of 8-12wt% to overcome bonding and brittleness defects. Through roller rotation and pulse stirring technology, the thickness deviation is kept within ±3% (L / D=20). Combined with nanoparticle anti-settling design, porosity is eliminated (porosity not exceeding 0.5%) to achieve uniform protection of the entire surface. At the same time, the use of chromium-free and cyanide-free formula reduces wastewater treatment costs by 60%, thereby systematically solving the above-mentioned problems of traditional processes.

[0017] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0018] Figure 1 This is a process flow diagram of a carbon fiber roller spray coating and plating production process according to the present invention;

[0019] Figure 2 This is a diagram showing the connection relationship of the core equipment in the carbon fiber roller spraying and coating production process of the present invention.

[0020] Figure 3 This is a collaborative diagram of key equipment for low-temperature chemical plating in a carbon fiber roller spraying and plating production process according to the present invention.

[0021] Figure 4 For the present invention Figure 1 A magnified view of the left half;

[0022] Figure 5 For the present invention Figure 1 A magnified view of the left half of the image. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] It should be noted that the terms "vertical," "horizontal," "up," "down," "left," "right," and similar expressions used in this article are for illustrative purposes only and do not represent the only possible implementation.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to limit the invention; the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0026] like Figure 1 and Figure 2 As shown, a composite chemical plating process for carbon fiber roller surfaces includes the following steps: (1) Plasma etching activation: Under a vacuum environment of 0.1-10 Pa, an argon / oxygen mixed plasma with a power of 1-5 kW is used to etch the carbon fiber roller substrate for 10-30 minutes, so that the surface roughness is increased to Ra1.0-3.0 μm and oxygen-containing functional groups are generated. The gas ratio of the plasma is Ar:O2=4-6:1, and the surface oxygen content is increased to 15-25 at% after etching; (2) Catalytic activation: The roller body treated in step (1) is immersed in a palladium-tin colloidal activation solution, wherein Pd 2+ Concentration of 50-200 mg / L, Sn 2+ The concentration is 1-5 g / L, the pH value is 1.5-2.5, and the nano-palladium catalyst layer is formed by deposition for 5-15 minutes under the ultrasonic assistance of a frequency of 40-100 kHz; (3) Low temperature composite chemical plating: The activated roller is placed in the chemical plating solution for plating. The plating conditions are a temperature of 65-85℃ (20-30℃ lower than the traditional process), a pH value of 4.5-5.5, a roller rotation speed of 10-30 rpm, a plating time of 60-180 minutes, and the plating solution is pulsed and stirred. Specifically, the stirrer is turned on and off alternately at a frequency of 5-10 Hz, with each cycle being turned on for 30 seconds and off for 10 seconds; (4) Post-treatment: The plated roller is cleaned with deionized water, heat-treated for 1-2 hours under hot air circulation at 180-220℃, and finally mechanically polished until the surface roughness Ra≤0.1μm.

[0027] In this implementation scheme, each step is sequentially connected to form a complete process chain: the carbon fiber roller substrate activated by plasma etching in step (1) directly enters the catalytic activation step (2). The palladium-tin colloidal activation solution deposits a nano-palladium catalytic layer on the rough surface formed by etching under ultrasonic assistance. The activated roller is then placed in the chemical plating solution in step (3). The composite coating is deposited under the set temperature, pH value and roller rotation and pulse stirring conditions. Finally, the finished product is processed by cleaning, heat treatment and polishing in step (4). The specific ratio of argon / oxygen mixed plasma in step (1) is set to provide a suitable surface for subsequent catalytic layer adhesion. The nano-silicon carbide particles pretreated with silane coupling agent in step (3) are uniformly dispersed in the plating solution and work together with pulse stirring on the rotating roller surface. The nitrogen protection heat treatment and heating rate control in step (4) are connected to the post-plating cleaning process. From the key implementation points, plasma etching activation provides mechanical anchoring and chemical bonding sites for the coating by constructing a roughness of Ra 1.0-3.0 μm and a surface oxygen content of 15-25 at%, thereby increasing the bonding strength to ≥25 MPa; the ultrasonic-assisted palladium-tin catalytic system (40-100 kHz) promotes the uniform distribution of palladium nanoparticles and enhances the density of catalytic active sites; the low-temperature chemical plating process at 65-85℃ is lower than the Tg temperature of the carbon fiber resin matrix, combined with nitrogen-protected heat treatment (heating rate ≤5℃ / min, avoiding thermal decomposition and hydrogen embrittlement of the matrix, thus improving the matrix strength). Retention rate > 95%; the combination of roller rotation (10-30 rpm) and pulse stirring (5-10 Hz) ensures that the coating thickness deviation is ≤ ±3% (L / D = 20). The dispersion stability of nano-silicon carbide particles is improved after pretreatment with KH-550, and the porosity is controlled to ≤ 0.5% with the help of thiourea stabilizer (1-5 mg / L). In terms of innovation, the Ni-P-SiC composite coating with medium phosphorus content (8-12 wt%) balances hardness (HV800-1000) and ductility, and the toughening effect of nano-SiC particles increases the impact toughness by 50% (≥3 J / cm). 2 The chromium-free and cyanide-free formula reduces wastewater treatment costs by 60% and systematically solves the problems of substrate damage, hydrogen embrittlement risk, coating peeling and environmental compliance in traditional processes.

[0028] like Figure 2 and Figure 3As shown, in this process, the plating solution used in step (3) consists of 20-30 g / L nickel sulfate, 25-35 g / L sodium hypophosphite, 40-60 g / L of a composite complexing agent consisting of a combination of sodium citrate and glycine, and 5-15 g / L of nano-silicon carbide particles (the nano-silicon carbide particles have a particle size of 50-200 nm and are pretreated with silane coupling agent KH-550. The pretreatment method is to disperse the nanoparticles in an ethanol solution with a concentration of 1-5 wt%, sonicate for 30 minutes, and then centrifuge and dry). The surfactant is sodium dodecyl sulfonate 0.1-0.5 g / L and the stabilizer is thiourea 1-5 mg / L; the heat treatment in step (4) is carried out under a nitrogen protective atmosphere, with a heating rate ≤5℃ / min; the final coating is a Ni-P-SiC composite structure, with a phosphorus content of 8-12 wt%, a SiC dispersed phase ratio of 5-10 vol%, a coating thickness of 20-50 μm, a porosity ≤0.5%, and an adhesion strength ≥25 MPa (measured according to ASTM C633 standard).

[0029] In this embodiment, the components of the plating solution in step (3) work synergistically in a specific ratio: nickel sulfate, as a nickel ion supply source, forms a stable reaction system with sodium hypophosphite (reducing agent) under the action of a composite complexing agent (sodium citrate + glycine). The combination of sodium citrate and glycine regulates the deposition rate by complexing nickel ions. Sodium dodecyl sulfonate (surfactant) is adsorbed on the surface of nano-silicon carbide particles (particle size 50-200nm), and together with the hydroxylated surface formed by KH-550 pretreatment, it inhibits particle agglomeration. Thiourea (stabilizer) avoids spontaneous decomposition of the plating solution by selectively adsorbing on active sites. Each component is uniformly contacted with the rotating roller surface in the 65-85℃ plating solution with pulse stirring, and produces an interfacial reaction with the oxygen-containing functional groups formed in step (1) and the nano-palladium catalyst layer in step (2). From the implementation points, the concentration ratio of 20-30 g / L nickel sulfate and 25-35 g / L sodium hypophosphite balances the deposition efficiency and coating composition. The 40-60 g / L composite complexing agent ensures that the pH value is stable in the range of 4.5-5.5. The matching of the dosage of 0.1-0.5 g / L sodium dodecyl sulfonate and 5-15 g / L nano silicon carbide particles can increase the suspension rate of particles in the plating solution to more than 90%. In step (4), the nitrogen protective atmosphere and the heating rate of ≤5℃ / min work together to promote the diffusion of the coating and the substrate interface during the heat treatment at 180-220℃, while avoiding performance degradation caused by oxidation. In terms of innovation, this plating solution formulation, through its chromium-free and cyanide-free design and the highly efficient complexing ability of the composite complexing agent, reduces wastewater treatment costs by 60%. In the final Ni-P-SiC composite coating, the 8-12wt% phosphorus content gives the coating both the uniformity of an amorphous structure and appropriate crystallinity. The 5-10vol% SiC dispersed phase enhances the hardness to HV800-1000 through a dispersion strengthening mechanism. The 20-50μm thickness and ≤0.5% porosity ensure the integrity of the entire surface protection, while the ≥25MPa bonding strength (measured according to ASTM C633 standard) verifies the synergistic effect of each component on the strengthening effect of interfacial bonding. This further supplements and solves the problems of poor plating solution stability, uneven particle dispersion, and coating protection failure in traditional processes.

[0030] In practice, this process requires the use of existing vacuum plasma etching equipment (including a stainless steel vacuum chamber, RF power supply, and gas flow controller) to achieve precise control of the 0.1-10Pa vacuum environment and argon / oxygen mixed plasma. A CNC ultrasonic cleaning tank (500-1500W) provides 40-100kHz ultrasonic assistance. A chemical plating reaction tank (made of 316L stainless steel) equipped with a continuously variable speed rotation mechanism is used to place the rollers and achieve a rotation of 10-30rpm. A mechanical stirrer (with a pulse control module) performs a 5-10Hz pulse stirring action. A hot air circulating oven (with a nitrogen inlet and a programmable temperature control system) is used to achieve a temperature of 180-220℃. Heat treatment is followed by mechanical polishing using a metallographic polishing machine (equipped with diamond polishing paste and a wool polishing disc). Specific materials used include T700 grade carbon fiber reinforced epoxy resin composite material as the carbon fiber roller matrix; palladium chloride as the palladium salt and stannous chloride as the tin salt in the palladium-tin colloidal activation solution; nickel sulfate heptahydrate (NiSO4·7H2O); industrial-grade sodium hypophosphite (NaH2PO2·H2O); sodium citrate dihydrate (C6H5Na3O7·2H2O) and analytical grade glycine (NH2CH2COOH) in the composite complexing agent; β-SiC powder with an average particle size of 60nm as the nano-silicon carbide particles; and chemically pure sodium dodecyl sulfonate (C6H5Na3O7·2H2O) as the surfactant. 12 H 25 SO3Na), the stabilizer thiourea is reagent grade (NH2CSNH2), the silane coupling agent KH-550 is industrial grade γ-aminopropyltriethoxysilane, and the deionized water meets the GB / T6682 Class I standard.

[0031] Specifically, existing vacuum plasma etching equipment (such as a horizontal vacuum chamber with a built-in dual electrode plate and roller rotating fixture, equipped with a vacuum system consisting of a mechanical pump and a molecular pump to maintain a vacuum environment of 0.1-10 Pa, and adjusting the Ar to O2 gas ratio to 4-6:1 via a mass flow controller) is required. The carbon fiber roller substrate (e.g., T700 grade carbon fiber reinforced epoxy resin composite material) is fixed to the fixture, and etching is performed using a 1-5 kW radio frequency power supply. The catalytic activation step requires a thermostatic bath with an ultrasonic generator (power adjustable to 400-1000 W to match a 40-100 kHz frequency). The bath contains palladium chloride (providing Pd). 2+ ), stannous chloride (providing Sn) 2+The activation solution, adjusted to pH 1.5-2.5 with hydrochloric acid, is used to suspend the rollers vertically within it using a lifting clamp. Low-temperature composite chemical plating requires a reaction vessel (made of 316 stainless steel, volume 50-500L depending on roller size) equipped with magnetic stirring and pulse control modules. The vessel contains a variable-frequency roller rotation mechanism (driven by a servo motor, speed 10-30 rpm). The plating solution materials include nickel sulfate heptahydrate, sodium hypophosphite monohydrate, sodium citrate dihydrate, industrial-grade glycine, analytical-grade sodium dodecyl sulfate, chemically pure thiourea, and 99.9% pure 50-200nm nano-silicon carbide particles (pretreated with γ-aminopropyltriethoxysilane, KH-550, and dispersed in anhydrous ethanol). The plating solution is then transported through a vessel jacket. The hot water circulation system controls the temperature at 65-85℃, and the pH is monitored and adjusted to 4.5-5.5 in real time by a pH meter. In the post-treatment stage, a hot air circulation oven (with a nitrogen inlet and flow meter, nitrogen purity ≥99.99%) is used. The cleaned roller is placed on a tray and heated to 180-220℃ at a heating rate of ≤5℃ / min and kept at that temperature for 1-2 hours. Finally, it is mechanically polished by a CNC polishing machine (equipped with diamond wheels and wool polishing discs, using 800#, 1500#, and 3000# sandpaper and 0.5μm diamond polishing paste in sequence). The entire process is completed by a crane or robot to transfer the roller between the equipment. All tooling fixtures that come into contact with the solution are made of polytetrafluoroethylene or 316 stainless steel to avoid contamination.

[0032] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.

Claims

1. A composite chemical plating production process for carbon fiber roller surfaces, characterized in that, Includes the following steps: (1) Plasma etching activation: In a vacuum environment of 0.1-10 Pa, argon / oxygen mixed plasma with a power of 1-5 kW is used to etch the carbon fiber roller substrate for 10-30 minutes to improve the surface roughness to Ra1.0-3.0 μm and generate oxygen-containing functional groups. (2) Catalytic activation: The roller body treated in step (1) is immersed in a palladium-tin colloidal activation solution, wherein Pd 2 +Concentration of 50-200 mg / L, Sn 2+ With a concentration of 1-5 g / L and a pH of 1.5-2.5, a nano-palladium catalyst layer is formed by deposition for 5-15 minutes under ultrasonic assistance at a frequency of 40-100 kHz. (3) Low-temperature composite chemical plating: The activated roller is placed in a chemical plating solution for plating. The plating solution consists of: 20-30 g / L nickel sulfate, 25-35 g / L sodium hypophosphite, 40-60 g / L of a composite complexing agent consisting of a combination of sodium citrate and glycine, 5-15 g / L of nano-silicon carbide particles with a particle size of 50-200 nm, 0.1-0.5 g / L of sodium dodecyl sulfonate as a surfactant, and 1-5 mg / L of thiourea as a stabilizer. The plating conditions are: temperature of 65-85℃, which is 20-30℃ lower than that of the traditional process, pH value of 4.5-5.5, roller rotation speed of 10-30 rpm, and plating time of 60-180 minutes. (4) Post-treatment: The plated roller is cleaned with deionized water, heat-treated in hot air circulation at 180-220℃ for 1-2 hours, and finally mechanically polished until the surface roughness Ra≤0.1μm.

2. The composite chemical plating production process for carbon fiber rollers according to claim 1, characterized in that: In step (1), the gas ratio of the plasma is Ar:O2 = 4-6:1, and the oxygen content on the surface increases to 15-25 at after etching.

3. The composite chemical plating production process for carbon fiber rollers according to claim 1, characterized in that: The nano-silicon carbide particles in step (3) are pretreated with silane coupling agent KH-550. The pretreatment method is as follows: the nano-particles are dispersed in an ethanol solution with a concentration of 1-5wt%, ultrasonically treated for 30 minutes, and then centrifuged and dried.

4. The composite chemical plating production process for carbon fiber roller surface according to claim 1, characterized in that: In step (3), the plating solution is pulsed and stirred, specifically by alternately turning the stirrer on and off at a frequency of 5-10Hz, with each cycle being 30 seconds on and 10 seconds off.

5. The composite chemical plating production process for carbon fiber rollers according to claim 1, characterized in that: The heat treatment in step (4) is carried out under a nitrogen protective atmosphere, with a heating rate ≤5℃ / min.

6. The composite chemical plating production process for carbon fiber roller surface according to claim 1, characterized in that: The final coating is a Ni-P-SiC composite structure, with a phosphorus content of 8-12wt%, a SiC dispersed phase ratio of 5-10vol%, a coating thickness of 20-50μm, a porosity of ≤0.5%, and an adhesion strength of ≥25MPa, as determined by ASTM C633 standard.